Effect of Non-Coding Region RNA Gene XIST (X-Inactive Specific Transcript) on Human Breast Cancer - Umar, Liya Agustin (Biomedical Journal of Indonesia, 2021)
X chromosome is a sex chromosome found in both women and men. The inactivation of the X chromosome is linked to a non-coding region of RNA known as the XIST gene (X-inactive specific transcript). This gene is located in the X inactivation center (XIC X-inactive center). The XIST gene is a region that belongs to the RNA group, non-coding transcripts (NCT), also known as microRNA. Breast cancer (Breast Cancer) is a type of cancer that commonly affects women, but men can develop breast cancer, but the chances are small, about 1 in 1000. Breast cancer is a cancerous neoplasm that is malignant, and occurs in the mammary gland. The presence of a specific XIST gene on the X chromosome and the prevalence of breast cancer, which is mostly in women, raises the idea that there is an influence of this gene on breast cancer (breast cancer) in the epigenetic process. The XIST gene related to microRNA has an opportunity to be looked at because certain microRNAs have a greater or lesser level (concentration) in cancer cells than normal cells. This is a new opportunity to continue to be developed as a consideration for a new treatment method involving gene therapy.